Low copy numbers of complement C4 and C4A deficiency are risk factors for myositis, its subgroups and autoantibodies. Issue 2 (28th September 2022) - Zhou, Danlei; King, Emily H; Rothwell, Simon; Krystufkova, Olga; Notarnicola, Antonella; Coss, Samantha; Abdul-Aziz, Rabheh; Miller, Katherine E; Dang, Amanda; Yu, G Richard; Drew, Joanne; Lundström, Emeli; et al.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are a group of autoimmune diseases characterised by myositis-related autoantibodies plus infiltration of leucocytes into muscles and/or the skin, leading to the destruction of blood vessels and muscle fibres, chronic weakness and fatigue. While complement-mediated destruction of capillary endothelia is implicated in paediatric and adult dermatomyositis, the complex diversity of complement C4 in IIM pathology was unknown. Methods: We elucidated the gene copy number (GCN) variations of total C4, C4A and C4B, long and short genes in 1644 Caucasian patients with IIM, plus 3526 matched healthy controls using real-time PCR or Southern blot analyses. Plasma complement levels were determined by single radial immunodiffusion. Results: The large study populations helped establish the distribution patterns of various C4 GCN groups. Low GCNs of C4T ( C4T =2+3) and C4A deficiency ( C4A =0+1) were strongly correlated with increased risk of IIM with OR equalled to 2.58 (2.28–2.91), p=5.0×10 −53 for C4T, and 2.82 (2.48–3.21), p=7.0×10 −57 for C4A deficiency. Contingency and regression analyses showed that among patients with C4A deficiency, the presence of HLA-DR3 became insignificant as a risk factor in IIM except for inclusion body myositis (IBM), by which 98.2% had HLA-DR3 with an OR of 11.02 (1.44–84.4). Intragroup analyses of patients with IIM for C4 protein levels and IIM-related autoantibodies showed that those with anti-Jo-1 or with anti-PM/Scl had significantly lower C4 plasma concentrations than those without these autoantibodies. Conclusions: C4A deficiency is relevant in dermatomyositis, HLA-DRB1*03 is important in IBM and both C4A deficiency and HLA-DRB1*03 contribute interactively to risk of polymyositis.